Heat capacities and thermodynamics of formation of flat-Al13 nitrate – [Al13(OH)24(H2O)24](NO3)15·11H2O. (November 2015) - Reusser, Dana; Schliesser, Jacob; Elliott, William S.; Woodfield, Brian F.; Johnson, Darren W.; Navrotsky, Alexandra
Highlights: Δ H of an aluminum hydroxide cluster, flat -Al13, was measured with calorimetry. Its heat capacity at T  = (2 to 300) K was measured. Standard enthalpies, entropies, and free energies of formation are determined. A second order phase transition was observed near T  = 214 K. Abstract: We report enthalpies of formation from the elements and oxides, Δ f H ∘  = −(26195.31 ± 34.46) kJ · mol −1 and Δ f, ox H  = −(1402.09 ± 33.36) kJ · mol −1, for crystalline [Al13 (μ3 -OH)6 (μ2 -OH)18 (H2 O)24 ](NO3 )15 ·11H2 O(cr) ( flat -Al13 ) measured using aqueous solution room temperature calorimetry. This material is a nitrate salt of a polynuclear aluminum hydroxide ion with thirteen aluminum metal centers, Al13 15+ . Unlike the ε-Al13 7+ Keggin ion, it contains solely octahedrally coordinated aluminum in a more flat topology. We also report heat capacities from temperatures of (2 to 300) K on this flat -Al13 nitrate using a Quantum Design Physical Property Measurement System (PPMS). These measurements were used to calculate the standard molar entropy and subsequently the free energy of formation for this material. We observed that during the heat capacity measurements, the flat -Al13 sample underwent a second order phase transition near T  = 214 K.